RELATIONSHIP BETWEEN DIGITAL SKILL COMPETENCE AND LEARNING-LOSS MITIGATION IN STUDENT VIDEOGRAPHY COURSES OF COMMUNICATION SCIENCES STUDY PROGRAM PUTRA INDONESIA UNIVERSITY CIANJUR (UNPI) - Aminah Agustinah; Pupu Jamilah; Shofia Fardliyah Rahmah (Jurnal Scientia, 2023)
Digital skill is the ability to use technology and information from digital devices effectively and efficiently in various contexts, such as academic, career, and everyday life. Digital literacy, namely literacy rooted in computer literacy and information literacy. Learning loss is a term used to describe the loss of knowledge and skills, either in general or specific, or the occurrence of a decline in the academic process due to certain factors. Learning-loss mitigation is an effort in the process of recovering the critical period of learning due to the Covid-19 pandemic. The purpose of this study was to obtain an overview of the relationship between digital skill competencies and learning-loss mitigation in the videography course of students of communications science study program of the University of Putra Indonesia. This thesis is a quantitative research with descriptive analysis approach and simple regression analysis. The script of this study indicate that there is no significant relationship between digital skill competence and learning-loss mitigation in the videography course of students of communications science study program of the University of Putra Indonesia, Cianjur district.